Combination treatment with orlistat-containing nanoparticles and taxanes is synergistic and enhances microtubule stability in taxane-resistant prostate cancer cells - Souchek, Joshua J. (Mol Cancer Ther, 2017)
Taxane-based therapy provides a survival benefit in patients with metastatic prostate cancer, yet the median survival is less than 20 months in this setting due in part to taxane-associated resistance. Innovative strategies are required to overcome chemoresistance for improved patient survival. Here, NanoOrl, a new experimental nanoparticle formulation of the FDA-approved drug, orlistat, was investigated for its cytotoxicity in taxane-resistant prostate cancer utilizing two established taxane-resistant (TxR) cell lines. Orlistat is a weight loss drug that inhibits gastric lipases, but is also a potent inhibitor of fatty acid synthase (FASN), which is overexpressed in many types of cancer. NanoOrl was also investigated for its potential to synergize with taxanes in TxR cell lines. Both orlistat and NanoOrl synergistically inhibited cell viability when combined with paclitaxel, docetaxel, and cabazitaxel in PC3-TxR and DU145-TxR cells, yet these combinations were also additive in parental lines. We observed synergistic levels of apoptosis in TxR cells treated with NanoOrl and docetaxel in combination. Mechanistically, the synergy between orlistat and taxanes was independent of effects on the P-glycoprotein multidrug resistance protein, as determined by an efflux activity assay. On the other hand, immunoblot and immunofluorescence staining with an anti-detyrosinated tubulin antibody demonstrated that enhanced microtubule stability was induced by combined NanoOrl and docetaxel treatment in TxR cells. Furthermore, TxR cells exhibited higher lipid synthesis, as demonstrated by (14)C-choline incorporation, that was abrogated by NanoOrl. These results provide a strong rationale to assess the translational potential of NanoOrl to overcome taxane resistance.